(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The teaching of linguistic units embedded with national-cultural meaning presents a complex and multidimensional challenge for educators in second and foreign language acquisition. These units—idioms, proverbs, culturally loaded vocabulary, and expressions—reflect the historical, social, and psychological experiences of a people and are essential for developing both communicative competence and intercultural sensitivity in learners. The traditional focus on grammatical and lexical accuracy often overlooks the significance of cultural nuances that influence meaning and pragmatic use. This article examines the theoretical foundations, challenges, and methodologies involved in teaching language with culturally significant components. Drawing upon recent pedagogical studies, cross-cultural analyses, and classroom experiences, it explores the role of teachers as cultural mediators and the importance of selecting authentic, context-rich materials. Special attention is given to how linguistic units reflect national identity and worldview, as well as how their effective teaching fosters greater empathy and intercultural understanding. The article concludes with practical recommendations and strategies to support educators in embedding cultural components meaningfully into language instruction.